Effect of phthalazinone moiety on sulfonated poly(aryl ether ketone) membranes for water vapor permeability. (23rd November 2021) - Wang, Danhui; Zhang, Shouhai; Wang, Tao; Liu, Zhouyang; Liu, Zeyuan; Xu, Peiqi; Deng, Cong; Jian, Xigao
Graphical abstract: Highlights: Polymer membranes with different structures were prepared for water vapor removal. Phthalazinone moiety based membranes present higher water vapor permeance than SPEEK. SPPEK-P has the highest water vapor permeance (8.69 × 10 −3 g⋅h −1 ⋅cm −2 ) at 48 °C. Abstract: Membrane technology is widely used in many industries for water vapor removal, however, few membranes can maintain permeance and selectivity at higher temperature. Poly(aryl ether ketone) membranes including sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(phthalazinoneone ether ketone) (SPPEK) and sulfonated poly(phthalazinoneone ether ketone) containing pendant phenyl moieties (SPPEK-P) were prepared using the casting method. It was found that water uptake, swelling ratio and hydrophilicity increased as ion exchange capacity (IEC) increased. In particular, SPPEK-P-2 membrane with IEC of 1.54 mmol⋅g −1 showed the highest water uptake of 29.4% and the lowest water contact angle. Moreover, the properties of three kinds of membranes analyzed by Brunner-Emmet-Teller and dynamic vapor sorption suggested that SPPEK-P-2 membranes exhibited the highest specific surface area (43.3 m 2 ⋅g −1 ) and water vapor sorption ability (22.5%). Finally, through cup method SPPEK-P-2 membrane presented the highest water vapor permeance of 8.69 × 10 −3 g⋅h −1 ⋅cm −2 at 48 °C.